The Role of the Iranian Civil Aviation Organization in Maintaining Aviation Safety - Hossien Mohammadzadeh Garehbagh; Mansor Jabari; Hoseyn Rostamzad (Faṣlnāmah-i Pizhūhish-i Huqūq-i ̒Umūmī, 2020)
The rapid development of the aviation industry depends on the safety of aviation. Aircraft safety is one of the most important issues in aviation and is not only an internal matter, but also a transnational one due to its nature. The development of the aviation industry is not the same in all countries. Non-compliance with international regulations and standards affect other countries’ aviation safety and may lead to aviation accidents and incidents. No country can take steps to ensure air safety without considering other countries situation. Since the National Aviation Organization is the main body in charge of aviation safety and the implementation of these regulations in the country, this organization shall make efforts to perform its assigned duties. This article seeks to explore the role of this organization based on international recommendations and standards and national rules and regulations to ensure the safety of aviation.